Doğal taşlara yüzey koruyucu olarak sol-jel yöntemiyle nano katkılı kaplama geliştirilmesi - Tekin Eroğul, Gözde (My University, 2020)
Doğal taşlar, tuz kristalizasyonu, atmosferik etkileşim, taş gözeneklerinde suyun donması, taşın sürekli ıslanıp kuruması, rüzgâra bağlı etkiler, taş üzerinde mikroorganizmaların büyümesi, rüzgâra bağlı aşınma ve insan etkisi gibi faktörler yüzünden zaman içinde bozulmaya uğrarlar. Su doğal taşların bozulmasına yol açan en önemli sebeplerden biridir; çünkü su, tuzların taş içerisinde kristalleşmesine yol açarak taşların pul pul dökülmesine neden olur, atmosferik kirliliklerle reaksiyona girip asidik bileşikler oluşturarak taşların yüzeyini bozar, soğuk iklimlerde donarak taşların çatlamasına sebebiyet verir ve mikro organizmaların taş üzerinde büyümesine neden olur. Bu sebepten doğal taşların suyun aşındırıcı etkisine karşı korunması gerekmektedir. Doğal taşlara koruyucu kaplamalar uygulamak taşlara su girişini engellemenin en etkin yöntemlerinden biridir. Bunun için doğal taşlara koruyucu kaplama olarak hidrofobik ve süperhidrofobik kaplamaların her ikisi de uygulanabilmektedir. Hidrofobik kaplamalarda, temas açısı 90°'den büyük olduğundan damlalar küreler şeklinde yüzeyde kalır ve hidrofilik kaplamalardaki gibi emilmezler. Süper hidrofobik kaplamalarda ise temas açısı 140°nin üzerinde olup damlalar hava paketlerinin üzerinde kalırlar. Bu tip kaplamalar doğal taşlara su girişini önleyerek taşlarda suya bağlı bozunmaların olmasını engellerler. Süperhidrofobik ve hidrofobik kaplama üretmenin en basit ve düşük maliyetli yöntemlerinden biri sol-jel yöntemidir. Sol-jel yöntemi, moleküler başlangıç madde-lerinin hidroliz ve yoğunlaşmasına dayanan bir düşük sıcaklık prosesidir. Bu proses ile inorganik, inorganik-organik hibrit kaplamalar, yüksek saflıkta tozlar, fiberler, aerojeller, seramik ve camlar gibi çeşitli malzemeler üretilebilmektedir. Sol-jel yöntemiyle sentezlenen inorganik-organik hibrit kaplamalar doğal taşların yüzeylerinin korunmasında sıklıkla kullanılmaktadır. Burada, inorganik bileşen kaplamaya kimyasal direnç ve ısıl kararlılık sağlarken polimerik organik bileşen de kaplamaya hidrofobiklik sağlamaktadır. Nano tozlar da kaplama yüzeylerinde yarattıkları mikro-nano pürüzlülük nedeniyle kaplamaların hidrofobikliğini arttırlar. Bu tez çalışmasında, mermer yüzeyler için nano silika ve nano alümina katkılı inorganik-organik hibrit kaplamalar geliştirilmiştir. Organik bileşen olarak polidimetilsiloksan (PDMS), inorganik bileşen olarak da tetrametoksisilan (TMOS) kullanılmıştır. İlk yapılan çalışmalarda, PDMS oranı %10'da sabit tutularak nano silika katkı miktarları değiştirilmiş ve farklı nano silika miktarının temas açısına etkisi incelenmiştir. İkinci setteki çalışmalarda, yine PDMS oranı %10'da sabit tutulmuş ancak bu sefer nano silika tozu yerine nano alümina tozu kullanılarak farklı nano alümina miktarlarının ve farklı toz kullanımının temas açısına etkisi incelenmiştir. Üçüncü setteki çalışmalarda ise, nano silika oranı %1'de sabit tutularak farklı PDMS oranının temas açısına etkisi incelenmiştir. Daha sonra geliştirilen kaplamalar nem direnci ve UV yaşlandırma testlerine tabi tutularak optimum koşulları sağlayan kaplamalar belirlenmiştir. Yapılan deneyler sonucunda, optimum temas açısı değeri nem direnci testi öncesinde %1 nano silika %10 PDMS katkılı kaplama ile 145° olarak ölçülmüşken, nem testi sonrasında ise %3 nano silika %10 PDMS katkılı kaplamalı numunelerde 140° olarak ölçülmüştür. Nano silika katkılı formülasyonların çoğu test sonrasında da hidrofobik özelliklerini korurken nano alümina katkılı formülasyonlar nem direnci testi sonrasında bu özelliklerini kaybetmiştir. UV yaşlandırma testi öncesinde ve sonrasında numunelerin hiçbirinde gözle görülebilecek renk değişimi olmadığı gözlenmiştir.

Natural Stones deteriorate due to factors such as salt crystallization, interaction with atmospheric pollutants, the freezing of water inside the pores of the stone, frequent wetting and drying of the stone, weathering due to wind, the growth of microorganisms on the surface of the stone, and human effects. Water is one of the main causes of stone decay because water causes the stone to flake due to salt crystallization, reacts with atmospheric pollutants to form acidic compounds which deteriorate the surface of the stone, causes stones to crack by freezing inside the pores of the stone in cold climates, and causes microorganisms to grow on the surface of the stone. Therefore, natural stones should be protected against the abrasive effect of water. Applying protective coatings is one of the most effective ways of preventing water ingress into the stones. Both hydrophobic and superhydrophobic coatings can be applied on stones for this purpose. Hydrophobic coatings have contact angles ≥90°, where drops form spherical shapes at the surface, and are not absorbed as in the case of hydrophilic coatings. Superhydrophobic coatings have contact angles ≥140° where drops sit on top of air pockets, and bounce off from the surface. Such coatings prevent water penetration into natural stones and therefore, prevent water related degradation of natural stones. One of the simplest and most cost-effective methods of producing superhydrophobic and hydrophobic coatings is the sol-gel method. The sol-gel method is a low temperature process based on the hydrolysis and condensation of molecular precursors. A wide variety of materials can be produced by this process, such as inorganic, inorganic-organic hybrid coatings, high-purity powders, fibers, aerogels, ceramics and glasses. The inorganic-organic hybrid coatings synthesized by sol-gel method are frequently used for the surface protection of natural stones. Here, the inorganic component provides chemical resistance and thermal stability to the coating, while the polymeric organic component also provides hydrophobicity to the coating. Nanopowders increase the hydrophobicity of the coatings due to the micro-nano roughness they create on the coating surfaces. In this thesis, inorganic-organic hybrid coatings with nanosilica and nanoalumina additives were developed for the protection of the surfaces of marbles. Polydimethylsiloxane (PDMS) was used as the organic component and tetramethoxysilane (TMOS) was used as the inorganic component. In the first set of experiments, the amount of nanosilica additives was changed by keeping the amount of PDMS constant at 10% w/w and the effect of the amount of nanosilica (%0,1, 1, 3, 5) on the contact angle was investigated. In the second set of experiments, the amount of PDMS was again kept constant at 10% w/w, but instead of silica nano powders, the effect of the amount of nano alumina (%0,1, 1, 3, 5) powders on the contact angle was investigated. In the third set of experiments, the amount of nanosilica was kept constant at 1% w/w and the effect of the amount of PDMS (%5, 10, 20, 30) on the contact angle was investigated. Afterwards, the coatings which have the optimum conditions were determined by exposing the coatings to humidity resistance and UV aging tests. The humidity resistance tests were carried out at 40°C, %100 RH according to the Standard ISO 6270-2:2017 (Paints and varnishes- Determination of resistance to humidity-Part 2: Condensation (in cabinet exposure with heated water reservoir)) at constant humidity conditions for 96 hours. This standard was selected because it specifies the general conditions and procedures which need to be observed when testing coated specimens in constant or alternating condensation-water atmospheres. The UV resistance tests were conducted with a Suntest CPS+ UV cabinet consisting of a Xenon arc lamp, using UV filter at a BST of 60°C with an irradiation density of 555 W/m2 for 144 hours. UV filter was selected since most of the natural stones used in ancient monuments are usually used outdoors, and a BST=60°C was selected to be representitive of approximately 35-45°C air temperatures. An irradiation density of 555 W/m2 was selected originated from the standard ISO 4892-2:2013. After the humidity resistance test, the contact angle values of the coatings containing %0,1, 1, 3, 5 w/w Aerosil R972 powder, and %10 w/w PDMS; %0.1, 1, 3, 5 w/w Alu C powder, and %10 w/w PDMS, and %5, 10, 20, 30 w/w PDMS and %1 w/w Aerosil R972 powder were measured with Krüss DSA 100 drop shape analyzer to determine the resistance of the coatings to humidity. The coated marble samples exposed to humidity tests were analyzed with the optical microscope to determine if there was any loss of adhesion, cracking or delamination of the coatings. After the UV aging test, the colorimetric values of the coatings containing %0.1, 1, 3, 5 w/w Aerosil R972 powder, and %10 w/w PDMS; %0.1, 1, 3, 5 w/w Alu C powder, and %10 w/w PDMS, and %5, 10, 20, 30 w/w PDMS and %1 w/w Aerosil R972 powder were measured with a Digieye Measurement System to determine if there was any change of color in the coated samples due to UV radiation. The contact angle values of the samples weren't measured after the UV aging test since neither the coatings, nor the nano powder additives had photocatalytic properties. Both the humidity resistance and UV aging tests were also applied on marble samples coated with commercial hydrophobic consolidant BS 290, and the results of the contact angle, and colorimetric tests of this sample was compared with the results of the contact angle, and colorimetric tests of the samples coated with the developed formulations. As a result of the experiments, the optimum contact angle value was obtained with the formulation containing 10% PDMS, and %1 nanosilica powder (contact angle: 145°) before the humidity test, and 10% PDMS and %3 nanosilica powder (contact angle: 140°) after the humidity test. While most of the formulations containing nanosilica retained their hydrophobicity after the humidity test, formulations containing nanoalumina lost their hydrophobicity after the humidity test. There was no change in color perceivable to the naked eye before or after the UV aging test in any of the samples. Before the humidity test, when the results were compared with the commercial coating, it was observed that the formulations which contained %1, %3, %5 w/w Aerosil R972 nano silica powder and %10 w/w PDMS had higher contact angle values than the commercial sample before the humidity test. This was attributed to the hydrophobicity of the nano silica powders due to being modified with dimethyl dichlorosilane, and to the increase in roughness. Nevertheless, the contact angle values of the formulations which contained %0.1, 1, and %3 w/w Alu C nano alumina powders, and %10 w/w PDMS were measured to be lower for the %0.1, and %1 w/w nano alumina coating, and slighlty lower for the %3 w/w nano alumina coating than the commercial coating because the alumina powders weren't hydrophobically modified like the nano silica powders, and increased the contact angle values only by creating roughness. The contact angle values of the sample containing %1 Aerosil R972, and %5 w/w PDMS was lower, %10 w/w PDMS was higher, %20 , and %30 w/w PDMS was slightly higher than the commercial coating. Even though this result seemed to be contradictory at first due to the hydrophobic character of PDMS, the SEM images showed that higher amounts of PDMS caused the nanoparticles to accumulate on certain regions within the coating instead of an even distribution across the film. This was attributed to the increase in the viscosity of the coating due to the higher PDMS amount. After the humidity test, when the results were compared with the commercial coating, the formulations which contained %1, and %3 w/w Aerosil R972 nano silica powder and %10 w/w PDMS had slightly higher, and higher contact angle values than the commercial sample. The contact angle value of the %1 Aerosil R972 w/w coating decreased from 145° to 120° because of the loss of adhesion. The contact angle value of the %3 Aerosil R972 w/w coating maintained its contact angle at 140° because the network of nano silica powders homogenously distributed throughout the film didn't allow water vapor to infiltrate into the film, and cause loss of adhesion. Nevertheless, the contact angle value of the %5 w/w coating dropped from 135° to 80°, and eventhough the contact angle value of this coating was higher than the commercial coating before the humidity test, it became lower than that of the commercial coating after the humidity test. This was again attributed to the loss of adhesion of the coating, verified by the micro cracks shown by the optical microscope images. For the formulations, which contained nano alumina particles, a much higher reduction in the contact angle value was observed. Contact angle values of the samples which contained %3, and %5 w/w Alu C nano alumina powders dropped from 110°, and 120° to 55°, even though these samples had contact angle values slightly lower (%3 w/w), and slightly higher (%5 w/w) contact angles than the commercial sample before the humidity test. This was attributed to the hydrophilic nature of the nano alumina particles. Unlike nano silica particles, the nano alumina particles absorbed a lot of the condesed vapor in the humidity cabinet, which infiltrated into the film, and caused most of it to delaminate as shown in optical microscopy images. The loss in the contact angle values of the % 0.1 w/w, and %1 w/w nano alumina film were much lower (The contact angle value of the %0.1 w/w nano alumina film dropped from 90° to 75° for the %0.1, and from 100° to 85° for the %1 w/w coating.) most probably due to the lesser amount of hydrophilic nano alumina particles. For the coatings which contained %5, %10, %20, and %30 w/w PDMS, and %1 w/w Aerosil R972, the results showed that the reduction in the contact angle value decreased with increasing PDMS content. The contact angle value of the %5 w/w PDMS coating reduced from 100° to 55° after the humidity test, which showed that this amount of PDMS addition was not enough for the coating to have enough adhesion to the substrate to withstand the humidity test. When the PDMS content increased to %10 w/w, there was still a reduction in the contact angle value of 25°, nevertheless the coating was still hydrophobic after the humidity test. When the PDMS value was increased to %20 w/w, the contact angle value was measured to be 110°C with a reduction of 15°. When the PDMS content was %30 w/w there was no reduction in the contact angle value. It was measured to be 125° both before, and after the humidity test. Therefore, after the humidity test, both of the coatings which contained %1 w/w Aerosil R972 and %20, and %30 w/w PDMS showed superior hydrophobicity along with the coating which contained 3 w/w Aerosil R972 and %10 PDMS when compared to the commercial coating.
The development of nano additive coatings by the sol-gel method for the surface protection of natural stones
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2020
Keywords: Daldırma kaplama yöntemi; Dipping coating method; Yüzey hidrofobisitesi; Surface hydrophobicity; Nanoyapı malzemeleri; Nanostructured materials